Determination of volumetric plasma parameters from spectroscopic N II and N III line ratio measurements in the ASDEX Upgrade divertor. (7th December 2017) - Henderson, S.S.; Bernert, M.; Brezinsek, S.; Carr, M.; Cavedon, M.; Dux, R.; Lipschultz, B.; O'Mullane, M.G.; Reimold, F.; Reinke, M.L.
Abstract: The diagnosis of tokamak divertor plasmas is limited in the ability to understand the behaviour and role of impurities, central to the overall understanding of how the divertor plasma can be utilised to control the power exhaust. New methods have been developed to extract the N concentration as well as plasma characteristics; the use of three visible N II lines has been shown to provide a unique solution of the background plasma density and temperature. Those techniques are applied to data from two sightlines sampling horizontally across the outer divertor plasma. The plasma densities obtained from the N II line ratios during a scan of the divertor temperature in a partially detached H-mode plasma suggest that, as the temperature drops, the plasma density decreases further up the divertor leg while closer to the strike point the plasma density increases. The former is consistent with the emission zone moving from the private flux region into the scrape-off-layer plasma, and therefore sampling two different density regimes, while the latter is consistent with electron pressure conservation along a field line. With an approximate model of the length of the emission region, the N II divertor concentration is calculated in this discharge to be  ≈ 5 − 25 % . The single N III line ratio measurement available within the same spectral range is dependent on temperature and density and therefore cannot provide a unique solution of both.